Penerapan Model Inquiry Terbimbing untuk Meningkatkan Keterampilan Proses Sains dan Hasil Belajar pada Materi Fotosintesis Pratikum Cakram Daun (Floating Disk) Siswa Kelas XII IPA 1 MAN Insan Cendekia Kota Palu - Latief, Riskayati (Universitas Negeri Makassar, 2022)
Abstract. This research was a classroom action research that performed by planning, action, observation, and reflection in each cycle. The research objective was to show the application of guided inquiry learning model in improving student’s Science Process Skill and student’s cognitive learning outcomes at grade XII IPA 1 of MAN Insan Cendekia Kota Palu. This research was focused on floating leaf disk. The subject of research was students of XII IPA 1 of MAN Insan Cendekia Kota Palu that consist of 25 students. The instruments were students’ work sheet and science process skill, teacher and students’ activity sheet, and students’ cognitive result test. Data were obtained by observation, interview, test, and documentation. Data validation used triangulation method. Data were analyzed using qualitative descriptive technique. The results of the research showed that guided inquiry learning model improved students' science process skills. It was showed by the precentage average of science skill (observtion and conclusion skill) in cycle I was 78,84 % and in cycle II was 90,55% (improve 11,71%). The average of students’ test improved from 81,17% in cycle 1 to 87,51% in cycle 2. The improvement of students’ achievement was showed by the increase of students’ maximum score from 85,71% in cycle I to 96,42% in cycle II. and percentage of classical comprehend from 86.73% in cycle 1 to 88.32% in cycle 2.Keywords: guided inquiry, science process skills, practical, scientific work, learning achievement.